Comparative evaluation of serum apelin, visfatin, and lipid levels in overweight hypertensive patients on enalapril versus telmisartan therapy - Mina Khalid MOHAMMED; Ahmed Moyed HUSSEIN; Jehan Abdulwahab MOHAMMAD; Zainab Haitham FATHI (Romanian Journal of Medical Practice, 2024)
Objectives. Visfatin and apelin are two adipokines that recently gained a special interest in hypertension research as they may have a role in the pathogenesis of hypertension and are closely related to the renin-angiotensin system. This study aimed to evaluate the serum levels of apelin and visfatin in uncontrolled newly diagnosed hypertensive patients, controlled hypertensive patients managed by enalapril and controlled hypertensive patients managed by telmisartan. Patients and methods. The study population included 126 participants, who were divided into four groups established as healthy participants, newly diagnosed hypertensive patients, hypertensive patients managed by enalapril and hypertensive patients managed by telmisartan. Outcomes. Serum apelin levels reduced significantly in newly diagnosed hypertensive patients, with a significant increase in visfatin levels compared with control group. Enalapril-treated patients expressed significantly higher apelin levels with a significant reduction in visfatin levels compared with newly diagnosed. Apelin levels were significantly increased in enalapril-treated patients compared telmisartan-treated group. Additionally, a significant reduction in visfatin levels were found in telmisartan group compared with newly diagnosed hypertensive patients. Moreover, a significant positive correlation was found between HDL and visfatin in patients receiving treatment. Additionally, visfatin was negatively correlated with triglycerides and VLDL in the same patient group. Conclusions. In light of the data collected so far, whether visfatin and apelin play roles in the pathophysiology of hypertension remains unclear and further research is still required to fully understand its relevance. Nevertheless, high visfatin and low apelin levels appear to be intrinsic characteristics of uncontrolled hypertension, indicating that these adipokines could be potential biomarkers for this disease.